2013
DOI: 10.5840/jbee2013107
|View full text |Cite
|
Sign up to set email alerts
|

Public Relations Student Perceptions of Ethics

Abstract: Abstract. Public relations is often perceived as unethical, yet professional associations and educators position the industry as an ethical profession. The aim of this paper is to investigate the perceptions of public relations students (N = 45) in a communication school in Australia towards ethics. Research involving a survey and a focus group found that students perceived public relations ethics depended on a negotiation between practitioners' responsibilities to stakeholders and their client or employer org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…(2) Sukses atau tidaknya suatu institusi sangat dipengaruhi oleh elemen profesionalisme yang dimiliki oleh para manajer dan karyawannya terutama yang berhubungan dengan etika. (3) Perguruan tinggi mempunyai peran (role) yang sangat penting dalam rangka mengembangkan profesinalisme dan etika dalam organisasi (Fitch, 2013).…”
Section: Kajian Literaturunclassified
“…(2) Sukses atau tidaknya suatu institusi sangat dipengaruhi oleh elemen profesionalisme yang dimiliki oleh para manajer dan karyawannya terutama yang berhubungan dengan etika. (3) Perguruan tinggi mempunyai peran (role) yang sangat penting dalam rangka mengembangkan profesinalisme dan etika dalam organisasi (Fitch, 2013).…”
Section: Kajian Literaturunclassified
“…A lot of discussion also focuses on the merit and extent to which business ethics education can be integrated with the business school's curricula (Bampton and Cowton, 2002;Sims and Brinkmann, 2003). Fitch (2013) reported enhancement of ethical understanding over the course of study in a public relations course. Nonna and Mladenovic (2015) indicated that the integrated ethics component enhances student's ethical sensitivity, though escalation in students' ethical judgement is more if they have not been earlier exposed to the framework.…”
Section: Impact Of Ethics Educationmentioning
confidence: 99%